Molecular detection and phylogenetic analysis of tick‐borne encephalitis virus in ticks in northeastern China. Issue 2 (8th September 2021) - Li, Xiaohui; Ji, Hongwei; Wang, Di; Che, Lihe; Zhang, Li; Li, Liang; Yin, Qing; Liu, Quan; Wei, Feng; Wang, Zedong
Abstract: Tick‐borne encephalitis virus (TBEV) is an important causative agent that causes neurological infections in humans and animals. In recent years, only few epidemiological surveys on TBEV have been conducted in China. The purpose of this study was to determine the prevalence and subtype of TBEV in ticks in northeastern (NE) China. A total of 3799 questing ticks were collected in NE China between April 2015 and June 2016. Ticks were pooled and tested for TBEV RNA using semi‐nested reverse transcriptase‐polymerase chain reaction. Positive pools were used to isolate the virus and amplify complete sequences, followed by sequence identity and phylogenetic analysis. TBEV RNA was detected in Ixodes persulcatus ticks at a total prevalence of 2.9% (6/143; 95% confidence interval: 1.2%–5.9%). Three TBEV strains were isolated (JL‐T75, HLB‐T74, and DXAL‐T83) and showed 93.9%–99.1% nucleotide identities and 97.1%–99.5% amino acid identities in Far Eastern (FE) TBEV subtypes, and 82.9%–87.6% nucleotide identities and 92.9%–96.4% amino acid identities in other subtypes. For polyprotein, the JL‐T75, HLB‐T74, and DXAL‐T83 strains showed 29, 50, and 55 amino acid residues, respectively, different from those in the TBEV vaccine (Senzhang) strain in China. Phylogenetic analysis revealed that these viruses were clustered in the FE‐TBEV branch but formed distinct clades depending on the natural foci. The results of this study suggest that the FE‐TBEV subtype is still endemic in I. persulcatus ticks in NE China, and the viruses in different natural foci in NE China are more likely to have genetic differences. Highlights: FE‐TBEV subtype is still endemic in I. persulcatus ticks in northeastern (NE) China with a total prevalence of 2.9%. TBEV in different natural foci in NE China are more likely to have genetic differences. Genetic differences may not affect the immunological protection of vaccination with the Senzhang strain in NE China.